Construct Validation of a School Principal Decision-Making Styles Scale (Malaysian Journal of Learning and Instruction, 2008)
Whereas substantial research in decision-making styles has focused on the theoretical and conceptual definitions, relatively less empirical attention has been paid to the development of its measures. Thus, the purpose of this study is to develop and validate a measure of school principal decision-making styles based on Vroom and Yetton’s (1973) theoretical framework. The researcher initially developed a 40-item pool of the Principal Decision-Making Styles Scale (PDMSS), and then these 40 items were reduced to 27 items after experts’ examination of its content validity. These 27 refined items were administered to 120 primary school principals in the northern states of Malaysia. In order to examine the construct validity of the PDMSS, a factor analysis employing principal component extraction procedures with varimax rotation was used. The factor analysis resulted in a 19-item instrument that measures three extracted decision-making styles, namely, autocratic, participative, and delegation. Additionally, the item analysis showed acceptable internal consistency reliability for the overall and the three specific sub-scales of PDMSS. Moreover, the confirmatory factor analysis revealed that the three identified styles indicate a good model fit.